South China Sea Disputes: KL’s Subtle Shift on China? - Oh, Ei Sun (2015)
Malaysia raised its level of response over a recent encounter with a Chinese vessel in disputed waters in South China Sea. Does this signify a new norm in Malaysian and other Southeast Asia claimants’ attitudes in engaging China?